High occurrence of length heteroplasmy in domestic Bactrian camel (Camelus bactrianus) - Xiaohong He; Xiaofei Chen; Wenbin Zhang; Yabin Pu; Shen Song; Han Jianlin; Kunzhe Dong; Qian-Jun Zhao; Weijun, Guan; Yuehui Ma; Lin Jiang (Informa UK Limited, 2017)
Heteroplasmy is the presence of more than one mitochondrial DNA (mtDNA) variant within a cell, tissue, or individual. In this study, sequence variation was investigated in the control region (CR) of mitochondrial DNA (mtDNA) from 135 individuals belonging to five primary domestic Bactrian camel breeds in China and Mongolia. Due to variation of the repeat unit G(T/C)(AC)n, length heteroplasmy was detected within each camel by direct sequencing and fragment analysis. A high occurrence of mtDNA heteroplasmy, up to 100 percentages was observed in five camel populations. Our study provides the first evidence of extensive length heteroplasmy in Bactrian camels.